2003
DOI: 10.1046/j.1365-3156.2003.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria dipsticks beneficial for IMCI in Cambodia

Abstract: Summaryobjectives The Integrated Management of Childhood Illness (IMCI) approach and new clinical treatment guidelines to control malaria among children less than 5 years old were introduced recently in Cambodia. This study was conducted to finalize the malaria part of the national IMCI fever chart.methods A total of 323 sick children 2-59 months old were studied at rural health centres in northern Cambodia from February to April 2000. Cases with fever (by axillary temperature or history) or anaemia (by palmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Few studies have been carried out specifically on the use of RDTs in the case management of sick African children less than 5 years old in areas of intense malaria transmission (Tarimo et al, 2001;Rimon et al, 2003). The statistical kappa test showed a very good significant association between RDT/MIC (0.81, p<0.0001) and RDT/PCR (0.84, p<0.0001) and a good significant agreement between PCR/MIC (0.77, p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been carried out specifically on the use of RDTs in the case management of sick African children less than 5 years old in areas of intense malaria transmission (Tarimo et al, 2001;Rimon et al, 2003). The statistical kappa test showed a very good significant association between RDT/MIC (0.81, p<0.0001) and RDT/PCR (0.84, p<0.0001) and a good significant agreement between PCR/MIC (0.77, p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies in other endemic areas have been conducted specifically in children so far [12-16]. In one study an increased sensitivity of a HRP-2 assay in children compared to adults was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…However, in sites without a microscope and trained personnel, malaria dipsticks may soon find an important role in the diagnosis of patients with fever. With increasing resistance to commonly used antimalarial drugs and the need to change to more costly combination therapy, cost-benefit is now a subject for discussion and the more accurate diagnosis of malaria, as opposed to the blind treatment of all patients with fever, has become an important consideration in rural health programmes (2).…”
mentioning
confidence: 99%